Integrating Technology Acceptance Model, Trust, and App Engagement - Timothy Calvin; Rio Rinaldo; Yosa Wiseso Raharjo; Jerry S. Justianto (JURNAL ECONOMINA, 2026)
The rapid growth of e-wallet adoption in Indonesia has intensified competition among providers, making customer loyalty increasingly difficult to maintain. This study investigates how data security, perceived ease of use, and perceived usefulness influence customer loyalty through user trust and app engagement. Drawing on the Technology Acceptance Model (TAM), trust theory, and engagement theory, data were collected from 233 active e-wallet users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all proposed relationships are significant. Data security is the strongest predictor of user trust (β = 0.661), outperforming perceived ease of use and perceived usefulness. User trust positively influences app engagement (β = 0.570), while app engagement has the strongest direct effect on customer loyalty (β = 0.546). Furthermore, app engagement partially mediates the relationship between trust and loyalty, accounting for 60.7% of the total effect. The findings suggest that loyalty in digital payment platforms is formed through a sequential process in which technology and security perceptions build trust, trust fosters engagement, and engagement strengthens loyalty. This study contributes to the literature by highlighting the central role of data security and app engagement in explaining loyalty formation in competitive digital payment environments.